Simplified Unified Model for Estimating the Motion of Magnetic Nanoparticles Within Electrohydrodynamic Field - Seo, Hyeon-Seok; Lee, Sangyoup; Lee, Jong-Chul (AMER SCIENTIFIC PUBLISHERS, 2014)
In previous research, we studied the electrical breakdown characteristics of a transformer oil-based magnetic fluid; mailnly, those were carried out by the experimental measurements. The first study was aimed at enhancing the dielectric breakdown voltage of transformer oil by adding magnetic nanoparticles experimentally under the official testing condition of dielectric liquids. The next study was focused on explaining the reason why the dielectric characterisitics of the fluids were changed through optically visualizing the particles motion in a microchannel using an optical microscopic measurement and numerically calculating the dielectrophoretic force induced in the fluids with considering only the properties of magnetic nanoparticles. In this study, we developed a simplified unified model for calculating further the motion of magnetic nanoparticles suspended in the presence of electrohydrodynamic field using the COMSOL multiphysics finite element simulation suite and investigated the effects of magnetic nanoparticle dielectrophoretic activity aimed at enhancing the electrical breakdown characteristics of transformer oil.
Keywords: DIELECTRIC-BREAKDOWN